Emergency medicine resident clinical experience vs. in‐training examination content: A national database study. Issue 2 (10th March 2022) - Kizziah, Melinda A.; Miller, Krystin N.; Bischof, Jason J.; Emerson, Geremiha; Khandelwal, Sorabh; Mitzman, Jennifer; Southerland, Lauren T.; Way, David P.; Hunold, Katherine M.
Abstract: Objectives: Emergency medicine (EM) residents take the In‐Training Examination (ITE) annually to assess medical knowledge. Question content is derived from the Model of Clinical Practice of Emergency Medicine (EM Model), but it is unknown how well clinical encounters reflect the EM Model. The objective of this study was to compare the content of resident patient encounters from 2016–2018 to the content of the EM Model represented by the ITE Blueprint. Methods: This was a retrospective cross‐sectional study utilizing the National Hospital Ambulatory Medical Care Survey (NHAMCS). Reason for visit (RFV) codes were matched to the 20 categories of the American Board of Emergency Medicine (ABEM) ITE Blueprint. All analyses were done with weighted methodology. The proportion of visits in each of the 20 content categories and 5 acuity levels were compared to the proportion in the ITE Blueprint using 95% confidence intervals (CIs). Results: Both resident and nonresident patient visits demonstrated content differences from the ITE Blueprint. The most common EM Model category were visits with only RFV codes related to signs, symptoms, and presentations regardless of resident involvement. Musculoskeletal disorders (nontraumatic), psychobehavioral disorders, and traumatic disorders categories were overrepresented in resident encounters. Cardiovascular disorders and systemic infectious diseases were underrepresented. When residents were involved with patient care, visits had a higher proportion of RFV codes in the emergent and urgent acuity categories compared to those without a resident. Conclusions: Resident physicians see higher acuity patients with varied patient presentations, but the distribution of encounters differ in content category than those represented by the ITE Blueprint.